Cryptosporidium in dairy cattle from a commercial farm Pahang - Hisamuddin, Nur Hazirah; Hashim, Najat; Soffian, Sharmeen Nellisa; Raja Abdul Rahman, Raja Nur Rahifah Inani; Barudin, Mohd Aiman; Abdul Wahab, Ridhwan; Mohammad, Mardhiah; Md Isa, Muhammad Lokman; Mat Yusof, Afzan (2016)
Cryptosporidium, a protozoan parasite can cause cryptosporidiosis which is a gastrointestinal disease that can infect human and livestock. Therefore, the study attempts to find the occurrence of Cryptosporidium infection in cattle in a commercial farm located in Kuantan, Pahang. A total of 151 faecal samples from cattle were collected. The samples were processed by using formol-ether concentration technique and stained by modified Ziehl-Neelsen. The result showed that 15.9% (24/151) cattle were positive for Cryptosporidium infection. The findings of this study suggested that proper hygiene practices must be applied in the farm to reduce the Cryptosporidium infection among cattle.